How to be Singaporean: becoming global national citizens and the national dimension in cosmopolitan openness. (8th August 2019) - Thian, Wen Li
ABSTRACT: This paper looks at how cosmopolitanism is practised amongst Singaporeans who have experienced Singapore's education reform in the 1990s. Cosmopolitanism in Singapore is tied to state-intervention with a national orientation. To complement Singapore's push towards cosmopolitanism, the education reform in the 1990s promoted the idea of a national citizen with a global orientation. I looked at 40 Singaporeans born after the year 1990 to investigate cosmopolitan attitudes that have emerged from the tensions between cosmopolitanism and nationalism. To meet the state's ideals of cosmopolitanism, these Singaporeans employed strategies to practice a particular form of cosmopolitan openness which prioritise national interests. Nationalism and cosmopolitanism co-exist in Singapore and share a dialectic relationship as I argue that these Singaporeans are global national citizens.